Crystalline Al1-xTix phases in the hydrogen cycled NaAlH4+0.02TiCl3 system - Pitt, M; Vullum, P; Sorby, M; Emerich, H; Paskevicius, Mark; Buckley, Craig; Gray, E; Walmsley, J; Holmestad, R; Hauback, B (Taylor & Francis, 2012)
The hydrogen (H) cycled planetary milled (PM) NaAlH4 + 0.02TiCl3 system has been studied by high resolution synchrotron X-ray diffraction and transmission electron microscopy during the first 10 H cycles. After the first H absorption, we observe the formation of four nanoscopic crystalline (c-) Ti-containing phases embedded on the NaAlH4 surface, i.e. Al2Ti, Al3Ti, Al82Ti18 and Al89Ti11, with 100% of the originally added Ti atoms accounted for. Al2Ti and Al3Ti are observed morphologically as a mechanical couple on the NaAlH4 surface, with a moderately strained interface. Electron diffraction shows that the Al82Ti18 phase retains some ordering from the L12 structure type, with the observation of forbidden (100) ordering reflections in the fcc Al82Ti18 lattice. After 2 H cycles the NaAlH4 + 0.02TiCl3 system displays only two crystalline Ti-containing phases, Al3Ti and Al89Ti11. After 10 H cycles, the Al89Ti11 is completely converted to Al85Ti15. Al89Ti11, Al85Ti15 and Al3Ti do not display any ordering reflections, and they are modeled in the A1 structure type. Quantitative phase analysis indicates that the Al3Ti proportion continues to increase with further H cycles. The formation of Ti-poor Al1 − x Ti x (x < 0.25) phases in later H cycles is detrimental to hydrogenation kinetics, compared to the starting Ti-richer near-surface Al2Ti/NaAlH4 interface present during the first absorption of hydrogen.